Letter (copy) : Spain - Citrine, Walter, 1887-1983
011-0100-001 WMC/WJB/AC/641 International Registered 19th April 1937 Mr. G. Stolz, International Federation of Trade Unions, 9, avenue d'Orsay, Paris VIIe. Dear Comrade Stolz, SPAIN. I am much obliged to you for sending to me the papers which you brought back with you when you returned from Spain. I have examined them with much interest; they help to prove the charge of intervention on the part of the Fascist Powers. I an returning them herewith as requested, also the showing the position of the forces at the time of your visit. Yours faithfully, General Secretary. Papers Map 292/946/11/100